2008
DOI: 10.1111/j.1551-2916.2008.02479.x
|View full text |Cite
|
Sign up to set email alerts
|

Borate Volatility from SOFC Sealing Glasses

Abstract: The volatility of borate species from glasses developed for solid oxide fuel cell seals was studied using thermodynamic calculations and compared with experimental results. Vapor pressure diagrams were used to identify the most volatile compounds under a range of expected operational conditions, e.g. oxidizing and reducing atmospheres with water vapor, at temperatures in the range of 7001-10001C. The species with the highest vapor pressures were BO 2 (g) under dry conditions and B 3 H 3 O 6 (g) under wet, redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 14 publications
(17 reference statements)
3
29
0
Order By: Relevance
“…Some compositions of glasses employed as sealants in SOFC are summarized in Table 2, and selected properties are provided in Table 3. Table 3 continued Glass code Metals commonly employed as interconnects in fuel cell designs include various austenitic and ferritic stainless steels, for example, Fe20Cr and FeCrAlY alloys, in addition to Ni-based superalloys, as summarized in [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], together with some BaO-free silicate glasses [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89]. Low-silica and silica-free borate-based compositions have also been reported [90][91][92][93].…”
Section: Sofc Alloysmentioning
confidence: 99%
“…Some compositions of glasses employed as sealants in SOFC are summarized in Table 2, and selected properties are provided in Table 3. Table 3 continued Glass code Metals commonly employed as interconnects in fuel cell designs include various austenitic and ferritic stainless steels, for example, Fe20Cr and FeCrAlY alloys, in addition to Ni-based superalloys, as summarized in [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], together with some BaO-free silicate glasses [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89]. Low-silica and silica-free borate-based compositions have also been reported [90][91][92][93].…”
Section: Sofc Alloysmentioning
confidence: 99%
“…Thermal stability of the silicates is typically high especially with low boron content [15]. The community in general agrees that alkali content must remain low for silicates to be viable sealant candidates to avoid volatilization and/or interaction with the SOFC electrolyte or interconnect.…”
Section: Introductionmentioning
confidence: 99%
“…The viscosity of invert glass systems is fragile, showing a large change in viscosity with small changes in temperature above T g, which could be catastrophic for a viscous glass seal if the seal design does not contain the molten glass and prevent its flow out of the seal region. Finally we note that boron-containing glasses, which have been widely used in rigid SOFC seals, may be unstable under wet H 2 environments, with some compositions exhibiting large weight losses [15,24].…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12][13][14] However, under the SOFC operation condition boron species from the borosilicate glass are highly volatile to form BO 2 under dry conditions and B 3 H 3 O 6 under wet, reducing conditions. 2,15 Earlier studies show that volatile species from glass sealants can significantly affect the microstructure of LSM electrodes.…”
Section: -3mentioning
confidence: 99%
“…8,[10][11][12][13][14] However, under the SOFC operation condition boron species from the borosilicate glass are highly volatile to form BO 2 under dry conditions and B 3 H 3 O 6 under wet, reducing conditions. 2,15 Earlier studies show that volatile species from glass sealants can significantly affect the microstructure of LSM electrodes.16 Komatsu et al 17 used glass to seal an anode-supported planar cell and found that the concentration of boron in the cathode exhaust gas trapped by a water condenser increased with the operation time during the long-term test at 800• C for 6500 h. We recently carried out a series of detailed studies on the effect of boron poisoning on electrode performance of the most common (La,Sr)MnO 3 (LSM), (La,Sr)(Co,Fe)O 3 (LSCF) and (Ba,Sr)(Co,Fe)O 3 (BSCF) cathodes, by heat-treating the electrodes in the presence of borosilicate glass. [18][19][20][21] Boron is chemically incompatible with the cathode materials, and preferentially reacts with the A-site cations in particular lanthanum to form insulating lanthanum borate, LaBO 3 .…”
mentioning
confidence: 99%